THOMAS ERNEST HULME AND LITERARY MOVEMENT IMAGISM - Javida A. Mamedova (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2020)
The beginning of the twentieth century is remembered in the world not only for a number of complex socio-political events, but also for the ups and downs in literature and art, which were created by the influences of those events. The multifaceted literary process in British literature of that period ended with the creation of a new historical page in world literature. The new stage in literature, which began with the end of the Victorian era (1837–1901), was caracterised by the emergence of various literary movements, new styles, and qualities of content, the new expression of modernist view of human and life, etc. This stage had many peculiarities. One of the most interesting literary events of that period was the emergence of the literary movement of imagism. As it is known, this literary movement, which emerged in protest against some feature of previous poetry, namely, numerous features of romantic poetry, Victorian poetry, has interesting complex creative principles. The article analyzes these principles and the main features of the imagism, taking into account the theoretical views of Thomas Ernest Hulme, one of the founders of this literary movement. It is known that one of the first samples of imagist poetry is Thomas Ernest Hulme’s poem “Autumn”. By analyzing this poem it is possible to find out the main distinctive qualities of imagism as a literary movement, thus defining the place of Thomas Ernest Hulme in British literature, and his effort to create new poetry. The stages of imagism, the thoughts of the other representatives of this movement as Ezra Pound, Frank Stuart Flint are analyzed. Although imagism as a literary movement did not last long, its influence on other literary movements and its important role in the development of British literature can be determined by analysing some of its qualities that are still relevant. With the outbreak of the war, in a difficult and tense situation caused by both material and spiritual problems, the publication of new works decreased, the current situation influenced artistic problems, making it necessary to find new approaches to human problems through the prism of other values. In such situation, the poems of the imagism style that are difficult to understand, with a hidden meaning, do not attract more attention of readers. Of course, people faced with the horrors of war, both at the front and in the rear, could not be interested in further observing the literary debate and its aftermath. Society now could no longer remain indifferent to the poems written in the trenches, describing the horrors of war, the tragedy experienced by a modern man, and since most of these works are written in the classic style, this form of poetry is becoming more and more obvious on the agenda, which ultimately , led to the decline of Imagism. Of course, these changes in literature are not limited to literary trends, and British poetry as a whole has been further developed, which is expressed in a variety of content and ideas